The role of Сentral Asia in world civilization - Uskembayeva, A.A.; Orazaeva, Zh.Zh. (KU Publ., 2021)
This article examines the concept of the nomadic civilization of the peoples of Central Asia. In the article, the authors consider the issue that the nomads of Central Asia had a triad of signs of civilization, including monumental architecture, writing and cities.The civilizational status of traditional nomadic societies should be associated with the existence in them of a special type of culture - the culture of pastoralists. The authors prove that a nomadic civilization existed in the Central Asian region, defining it as a socio-cultural formation, a "supersystem" that has taken a fairly strong place in human history. Central Asia is a point of the world connecting North and South, West and East, through which not only trade routes, like the Great Silk Road, diplomatic, research, and confessional missions passed from ancient times, but also from it the great conquests of the world began (Attila, Tamerlane, Babur). Tnis point stopped the historical campaign to the East of Alexander the Great, who founded the city of Iskenderabad (present-day Khujand in Tajikistan). Genghis Khan whose offspring played a great role in the history and culture of the region left a deep mark. All these interconnections have given rise to many cross-cultural values of the Central Asian civilization, giving it a special flavor of receptivity and openness.
Əлемдік өркениеттердің дамуындағы Орталық Азияның рөлі
Роль Центральной Азии в развитии мировой цивилизации
Keywords: civilization; Central Asia; nomad; region; world; history; culture